Restrospectiva a "enfoque": una réplica Raúl Gustavo Ferreyra - Ruas, Juan Carlos (2016)
"This essay has the main purpose of clarifying some ideas not elucidated in Raúl Gustavo Ferreyra's original work, showing other visions of what can be understood as "law" in purely axiological terms or as a legal system, and -finally- outlining my own vision of what could be "law" in Latin American experiences."